Effects of learning languages on volunteering - Ailina Makhmut Nursultankyzy; Natalya Nikolaevna Khan; Gulzhaina Kuralbaevna Kassymova; Ardak Kenesbayevna Kalimoldayeva; Elmira Kanatovna Ketebayeva (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2024)
Learning languages is an important aspect of modern times that influences people's thinking which was studied by many researchers. Today the knowledge of different languages is becoming an increasingly significant aspect of volunteering, having a profound impact on its various aspects. This article discusses the importance of knowing foreign languages for developing empathy, improving communication skills, and expanding the worldview of volunteers using a questionnaire consisting of 12 questions divided into three main sections (empathy, communication skills, and worldview). Each section includes four questions related to the specific aspect that are given randomly. Responses were received from random respondents from various universities in Kazakhstan in Almaty through the use of a Likert scale in the questionnaire. This article, based on the collected materials and the results of other studies, shows that learning languages has a positive effect on the development of empathy, as it helps to better understand a person, and their mood, and can help to imagine yourself in the place of another. In addition, it shows how knowledge of languages affects the development of communication skills in a volunteer, as it helps to better understand a person, be a good listener and at the same time maintain a conversation. The data also showed that learning languages can have a positive impact on the development of things like motivation and analytical thinking and encourages people to try new things.